A comparative study of organoid-derived and cell line-derived intestinal epithelial models - Melis Asal; Nanne J. Paauw; Hetty J. Bontkes; Sandra J. van Vliet; Reina E. Mebius; Susan Gibbs (PLoS ONE, 2026)
Background In vitro intestinal epithelial models are being developed for studying gut physiology, barrier function, and drug transport. There are two major in vitro models which are currently used: cell line-derived monolayers (such as Caco-2/HT29 cocultures) and primary cell monolayers derived from human intestinal organoids. Aim To conduct a side by side comparison of organoid-derived and cell line-derived intestinal epithelial monolayers, assessing their morphological features, barrier performance, and secretome under similar culture conditions. Methods Human duodenum-derived organoids and Caco-2/HT29 cocultures (9:1 ratio) were seeded onto Transwell inserts and were harvested at the same time for comparative analysis. Barrier function was assessed by transepithelial electrical resistance (TEER) and Lucifer Yellow permeability. Structural characterization was performed using immunofluorescence microscopy, scanning and transmission electron microscopy. Secretion of growth factors and chemokines was quantified on apical and basal sides via multiplex assays. Results Both models formed intact epithelial barriers with robust tight junctions and displayed appropriate apical-basolateral polarization, confirmed by the presence of microvilli. However, the organoid-derived model exhibited occasional villus-like protrusions and ultrastructural crypt-like invaginations, homogenous secretion of Mucin 2 over the surface, and release of epithelial growth factor whereas the cell line model exhibited longer and more densely packed microvilli and higher apical secretion of vascular endothelial growth factor. The barrier properties were comparable except that the organoid model had decreased permeability (Lucifer Yellow). Conclusions This study highlights key structural, functional, and molecular similarities and differences that influence the physiological relevance and application scope of each model. It enables educated decision making when choosing the best model for a particular “Context of Use” weighing the pros and cons between experimental convenience and physiological relevance.